A hybrid model of diffusion: international cooperation and domestic adoption of carbon capture and storage (CCS) within the People’s Republic of China (PRC) - McAlinden, Karl J. (2022)
As a suite of emerging technologies, carbon capture and storage (CCS) holds the potential to abate huge quantities of emissions from fossil fuel sources, making it appealing to industrialised nations seeking to mitigate climate change. Holding uncertainties around its technical viability and facing competition from low-carbon energy options, there is a need to enhance global learning and increase information sharing while removing hesitations through large-scale demonstrations. As international projects ran into difficulties, we saw a sharp increase in cooperation with China, hoping the country’s unique characteristics and circumstances might facilitate accelerated deployment. Despite showing enthusiasm, China demonstrated unclear appetite for the technologies, thus frustrating international partners.